Two novel eremophilane sesquiterpenes from an endophytic Xylariaceous fungus isolated from leaves of Cupressus lusitanica - Amaral,Luciana S. (2010)
Two new eremophilane sesquiterpenes, cupressolide A and cupressolide B, along with two known sesquiterpenes, has been characterized from the EtOAc extract of a liquid medium where a Xylariaceous fungus, isolated as an endophytic fungus from health tissues of Cupressus lusitanica leaves, was cultivated. The structures of the isolated compounds were determined by analyses of their MS and NMR spectroscopic data.